AKSIOLOGI : IMPLIKASI & KETERASINGAN ILMU DALAM FILSAFAT ILMU - AINOL (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
The topic of the problem in this paper is the axiology of implications and alienation of science in the philosophy of science between the three sets that form the basis for philosophy. Epistemology, ontology and axiology. Axiology is a theory of values ​​that are divided into ethical / moral (behavior) and aesthetic (beauty) values, where these two values ​​will be linked to the implications and alienation of science to value science and value-free science, including minimizing knowledge so that it does not get out of the responsibility of science. itself. Keywords: Axiology, morals, philosophy, science